The Use of Aversives in Special Education: Legal and Practice Considerations for School Principals. (December 2017) - Katsiyannis, Antonis; Losinski, Mickey; Whitford, Denise K.; Counts, Jennifer
The use of aversives as a method for behavioral intervention in U.S. public schools has been a persistent concern and often subject to litigation, particularly among students with disabilities. The use of aversives (restraint, seclusion, and corporal punishment) have been supported in some cases due to their perceived necessity to keep children and youth with disabilities from causing harm to themselves or others or as a pedagogical method for behavior change. However, research strongly supports the need for less use of aversives and instead a critical focus on the use of multitiered systems of support to prevent the escalation of behavior that may result in the use of aversives. This article provides a review of 173 legal cases from 1997 through 2016 that ruled on the use of aversives in public schools for children and youth with disabilities. The authors provide legal implications to schools that use aversives, as well as an alternative framework for school principals in lieu of using restraint, seclusion, and corporal punishment as methods for behavior intervention.